2017
DOI: 10.21474/ijar01/3484
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Pain Among Saudi Medical Students in Makkah.

Abstract: Objective: To determine the prevalence and associated risk factors for musculoskeletal pain among medical students in Saudi Arabia. Method: A cross-sectional analysis for one Saudi medical school in 2015-2016 academic year.Themain outcomes were measured byThe Nordic Musculoskeletal Questionnaire (NMQ) which was used to screen for pain in different anatomic joints during the past week and past year. Another questionnaire was developed to assess for contributing factors for the pain. Result: 849 medical students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(7 reference statements)
0
0
0
Order By: Relevance
“…Also, our study showed a significant association between smartphone addiction and LBP (p-value = 0.004), while multiple previous studies showed a significant association between smartphone addiction and other factors such as educational level and neck pain [ 4 , 11 ]. Furthermore, two other studies supported our finding that both neck and LBP ranked among the top three most prevalent areas of musculoskeletal pain over the course of one year [ 4 , 18 ]. However, over the course of one week, we found that only neck pain ranked among the top three most prevalent areas.…”
Section: Discussionsupporting
confidence: 89%
“…Also, our study showed a significant association between smartphone addiction and LBP (p-value = 0.004), while multiple previous studies showed a significant association between smartphone addiction and other factors such as educational level and neck pain [ 4 , 11 ]. Furthermore, two other studies supported our finding that both neck and LBP ranked among the top three most prevalent areas of musculoskeletal pain over the course of one year [ 4 , 18 ]. However, over the course of one week, we found that only neck pain ranked among the top three most prevalent areas.…”
Section: Discussionsupporting
confidence: 89%